Zirconium-cobalt hydrogen storage material and preparation method thereof

The preparation of spherical zirconium cobalt hydrogen storage powder through magnetic levitation smelting and rotary electrode powdering technology solves the problems of spontaneous combustion risks of hydrogen storage alloy materials and poor cyclicity of hydrogen storage performance, and achieves high safety and high hydrogen storage volume, which is suitable for applications with high stability and long life.

CN120272761AInactive Publication Date: 2025-07-08ZHONGKE YANNUO (BEIJING) TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510482601.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-17
Publication Date
2025-07-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing hydrogen storage alloy materials are prone to safety risks such as spontaneous combustion during manufacturing, transportation and processes, and the hydrogen storage performance is poor, making it difficult to meet the application needs of high stability and long life.

Method used

Magnetic levitation furnace is used to prepare zirconium cobalt alloy under vacuum environment, and combined with rotary electrode powder making technology, spherical zirconium cobalt hydrogen storage powder is prepared to avoid ball abrasion and crushing process, improve spherical shape and fluidity, reduce specific surface area, and ensure that the material is not easily powdered and oxidized.

Benefits of technology

The prepared spherical zirconium cobalt hydrogen storage powder has high spherical shape, low activity, high safety, high hydrogen storage capacity, and stable hydrogen absorption and discharge performance. It is suitable for high stability and long-life application scenarios, such as vehicle-mounted hydrogen storage systems, nuclear industry and aerospace.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120272761A_ABST
    Figure CN120272761A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of hydrogen absorption materials, and particularly relates to a zirconium-cobalt hydrogen storage material and a preparation method thereof. Zirconium and cobalt are mixed according to the molar ratio of 1: (0.99-1.01), a magnetic levitation smelting furnace is adopted for smelting in a vacuum environment, and the temperature is slowly increased to 1950-2200 DEG C for heat preservation; and after heat preservation is completed, the temperature is reduced to 300-350 DEG C at the cooling rate of 10-20 DEG C / min, then furnace cooling is carried out to the room temperature, then turning over is carried out, smelting is repeated for multiple times, a single-phase alloy ingot is obtained, a cylindrical alloy bar is obtained through machining, plasma rotating electronic atomization powder preparation is carried out, and the spherical zirconium-cobalt hydrogen storage powder is obtained. The prepared hydrogen storage alloy powder is ultrahigh in sphericity degree, high in yield, smooth, small in specific surface area, high in hydrogen storage capacity, not prone to pulverization and oxidation and good in hydrogen storage performance circularity, the problems that existing hydrogen storage alloy powder is prone to spontaneous combustion risks and poor in transportation and storage safety are solved, and the hydrogen storage alloy powder is suitable for scenes with the requirements for high stability and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of hydrogen storage materials, and particularly relates to a zirconium-cobalt hydrogen storage material and a preparation method thereof. Background Art

[0002] With the growth of the demand for clean energy, hydrogen energy has become an important option due to its high energy density and zero carbon emissions. Hydrogen storage technology is the key to the application of hydrogen energy. Compared with traditional high-pressure gaseous and cryogenic liquid hydrogen storage, solid hydrogen storage materials (such as zirconium alloys) have advantages such as high safety and high hydrogen storage density.

[0003] Existing hydrogen storage alloy materials mainly include several categories such as rare earth-based, magnesium-based, titanium-based, and zirconium-based. Each material has its own characteristics in terms of hydrogen storage performance, but there are also some obvious disadvantages.

[0004] Rare earth-based hydrogen storage alloys (such as LaNi5) have the advantages of easy activation and fast hydrogen absorption and desorption rates; however, their hydrogen storage capacity is relatively low (only 1.37 wt.%), making it difficult to meet the high energy density requirements. Moreover, the cost is high, as rare earth metals (such as La) are expensive. Although using mixed rare earth (Mm) can reduce the cost, it will affect the performance, and the cycle life is short. After hydrogen absorption, the lattice expands, leading to pulverization and rapid capacity decay. It is suitable for nickel-metal hydride batteries and small-scale hydrogen storage.

[0005] Magnesium-based hydrogen storage alloys (such as Mg2Ni, MgH2) have the advantage of high hydrogen storage capacity, but the hydrogen absorption and desorption temperature is high (generally >300 °C), the kinetic performance is poor, the cycle stability is poor, and they are prone to pulverization. It is necessary to improve through nanosizing or alloying (such as Mg-Ni, Mg-Fe). The hydrogen absorption rate of pure magnesium is slow, and mechanical alloying or catalysts (such as Ni, Fe) are required to improve the performance. It is suitable for solid-state hydrogen storage and hydrogen energy transportation.

[0006] Titanium-based hydrogen storage alloys (such as TiFe, TiMn2) have the advantage of cheap raw materials, but they have difficulties in activation, and a TiO2 passivation layer is easily formed on the surface. High-temperature and high-pressure pretreatment is required, the hysteresis effect is serious, the hydrogen absorption and desorption pressure difference is large, affecting reversibility, and they are sensitive to impurities and prone to poisoning. It is suitable for industrial hydrogen storage and hydrogen compressors.

[0007] Zirconium-based hydrogen storage alloys (such as ZrV2, ZrCr2) have the advantages of fast hydrogen absorption rate and long cycle life, but they have disadvantages such as high cost, expensive zirconium metal, poor stability, and being easily affected by the environment. It is suitable for fixed hydrogen storage and isotope separation.

[0008] Vanadium-based hydrogen storage alloys (such as VH2) have the advantage of relatively high hydrogen storage capacity, but vanadium is expensive, and commercialization is limited. It is suitable for medium-temperature hydrogen storage research.

[0009] Zirconium-cobalt hydrogen storage materials with different microstructures have significant differences in hydrogen storage performance, mechanical strength, and safety performance, and their application scenarios are also different. The existing conventional hydrogen storage alloy powders mainly adopt the ball milling and crushing process, and the obtained powders are irregular powders. Although the irregular zirconium alloy powders have many surface edges and corners, a large specific surface area, and are not smooth, it does not directly lead to low hydrogen storage capacity. However, they have high activity, which will exacerbate pulverization, cause oxidation and safety problems, and have poor cyclicity of hydrogen storage performance. They are prone to spontaneous combustion and other risks during manufacturing, transportation, and processes, are easy to oxidize, have poor safety in transportation and storage, have prominent use safety problems, and have poor cyclicity of hydrogen absorption and desorption performance. They are not suitable for large-scale applications and are not applicable to fields such as on-vehicle hydrogen storage, fixed hydrogen storage, nuclear industry, and aerospace. Summary of the Invention

[0010] Due to the high activity of conventional hydrogen storage alloy materials, there are risks such as spontaneous combustion during their manufacturing, transportation, and processes. In order to overcome the above deficiencies of the prior art, the purpose of the present invention is to provide a zirconium-cobalt hydrogen storage material and its preparation method. The obtained zirconium-cobalt hydrogen storage material has an ultra-high sphericity, a high yield, no edges and corners on the surface, a smooth surface, a small specific surface area, a high hydrogen storage capacity, reduced activity, is not easy to pulverize and oxidize, has good cyclicity of hydrogen storage performance, solves the problems that the existing hydrogen storage alloy powders are prone to spontaneous combustion risks during manufacturing, transportation, and processes, and have poor safety in transportation and storage, has high safety, good cyclicity of hydrogen absorption and desorption performance, is suitable for scenarios with high stability and long life requirements, and is a hydrogen storage alloy material applicable to fields such as nuclear industry and aerospace.

[0011] The present invention provides a preparation method for a zirconium-cobalt hydrogen storage material, which includes the following steps:

[0012] (1) Select elemental zirconium particles and elemental cobalt particles, and mix them in a molar ratio of 1:0.99 - 1.01 to obtain zirconium-cobalt mixed granular materials;

[0013] (2) Use a magnetic levitation melting furnace to melt the zirconium-cobalt mixed granular materials in a vacuum environment. The melting parameters are as follows: slowly heat up to 1950 - 2200 °C for heat preservation; after heat preservation, cool down at a cooling rate of 10 - 20 °C / min to 300 - 350 °C, and then cool with the furnace to room temperature to obtain a ZrCo alloy single-phase alloy ingot without other impurity phases;

[0014] (3) Through lathe processing, remove the surface layer of the ZrCo alloy single-phase alloy ingot obtained in step (2) to obtain a cylindrical cobalt-zirconium alloy rod. Perform plasma rotating electrode atomization powder making on the cobalt-zirconium alloy rod in a rotating electrode powder making device. After powder making, spherical zirconium-cobalt hydrogen storage powder with a target size of 50 - 150 um is obtained.

[0015] Due to the high activity of conventional hydrogen storage alloy materials, risks such as spontaneous combustion are likely to occur during their manufacturing, transportation, and processes. The present invention does not adopt the ball milling and crushing process. Instead, suitable raw materials are selected and cast to obtain a complete ingot, and then rotating electrode atomization is used to obtain spherical zirconium-cobalt hydrogen storage powder. By changing the preparation process, the present invention changes the microscopic morphology of the hydrogen storage material, improves the sphericity of the spherical powder. The prepared spherical zirconium-cobalt hydrogen storage powder has extremely high sphericity, good fluidity, less pollution, high yield, no edges and corners on the surface, a smooth surface, a relatively high hydrogen storage capacity, and the hydrogen storage capacity at 0.15 MPa can reach more than 2.8 wt%. More importantly, it reduces the specific surface area of the powder, reduces the activity of the hydrogen storage material, avoids the risks during manufacturing, transportation, and storage, is not prone to pulverization and oxidation, has good hydrogen storage performance cyclicity, solves the problems that existing hydrogen storage alloy powders are prone to spontaneous combustion risks during manufacturing, transportation, and processes, and have poor safety during transportation and storage, and has high safety.

[0016] The alloy bar required for preparing spherical powder is brittle and prone to cracking, which is a difficult problem encountered in the process of preparing spherical powder. During the research process, the inventor found that a zirconium-cobalt alloy with a molar ratio of 1:0.99 - 1.01 has good hydrogen storage performance and cyclic performance, is not prone to brittleness, is easy to form, is not prone to cracking during the casting and cooling process, and can obtain a complete ingot, solving the problem that the alloy bar required for preparing spherical powder is brittle and prone to cracking; when the zirconium content is too high, the surface activity is high, the safety during transportation and storage is poor, and the zirconium-cobalt alloy becomes brittle, and it will crack during the casting and cooling process of the alloy, making it difficult to obtain a complete ingot required for powder making; when the zirconium content is too low, the hydrogen storage performance is relatively low. In addition, during the research process, the inventor found that when preparing a ternary alloy hydrogen absorption material by adding 5 - 10% molar ratio of V, Fe, Mn, Mg, Ni, and rare earth elements to this zirconium-cobalt alloy respectively, the alloy components are all brittle during actual melting, and it is difficult to obtain a complete ingot meeting the powder making requirements.

[0017] The zirconium-cobalt alloy hydrogen storage material prepared by the present invention has mild hydrogen absorption and desorption reaction conditions, can still maintain high performance after multiple hydrogen absorption and desorption cycles, and performs well in high-temperature and corrosive environments.

[0018] The melting parameters in step (2) are to slowly heat up to 1950 - 2200 °C for heat preservation; after the heat preservation is completed, cool down to 300 - 350 °C at a cooling rate of 10 - 20 °C / min, and then cool with the furnace to room temperature. Using the above conditions can ensure obtaining an alloy ingot with high uniformity, no segregation, no cracks or fractures. If the heat preservation temperature is too high or too low, it will affect the uniformity of the obtained ingot; and the cooling rate is also relatively important. If the cooling rate is too fast, when the cooling rate reaches 30 °C / min and above, the surface of the ingot cools too fast, which will cause the internal stress of the alloy to accumulate, generate tensile stress, increase the brittleness of the alloy, and form cracks or directly crack.

[0019] The present invention uses plasma rotating electron atomization (PREP) to prepare powder, resulting in powder with extremely high sphericity, a relatively high yield of coarse powder (50 - 150 μm), extremely high sphericity, high roundness, and no edges or corners, solving problems such as high activity, easy spontaneous combustion, overly large particle size, overly small specific surface area, and overly low hydrogen absorption rate.

[0020] During the research process of the present invention, a large amount of research was conducted on the powder preparation method.

[0021] (1) Irregular powder: The ball milling and crushing process is mainly used, and the obtained powder is irregular powder with many surface edges and corners, a large specific surface area, and not smooth. Although it will not directly lead to low hydrogen storage capacity, it will exacerbate powdering, causing oxidation and safety problems, with prominent oxidation, transportation, and use safety problems. At the same time, the cyclicity of hydrogen absorption and desorption performance is poor, and it is not suitable for large-scale applications.

[0022] (2) Spherical powder: Prepared by gas atomization method. Gas atomization powder preparation mainly has two types:

[0023] 1) By the VIGA (Vacuum Induction Melting Gas Atomization) process. In the VIGA (Vacuum Induction Melting Gas Atomization) process, the metal is melted in a ceramic / graphite crucible in a vacuum induction furnace. Since zirconium cobalt alloy has a certain activity and will react with the crucible, it is not suitable for the powder preparation of the present invention.

[0024] 2) EIGA (Electrode Induction Melting Gas Atomization) powder preparation. The powder obtained by EIGA (Electrode Induction Melting Gas Atomization) powder preparation has a relatively low sphericity, the obtained powder is finer, and the yield of coarse powder (50 - 150 μm) is relatively low, generally below 50%, so it is not suitable for the present invention.

[0025] Preferably, the present invention selects zirconium single - element particles with a purity of 99.96% and cobalt single - element particles with a purity of 99.95%, and uses high - purity cylindrical single - element particles as alloy raw materials. The specifications of the zirconium single - element particles are cylindrical particles with a diameter of 3 mm and a length of 3 mm; the specifications of the zirconium single - element particles are cylindrical particles with a diameter of 3 mm and a length of 3 mm. The specific surface area of cylindrical single - element particles of this specification is regular and easy to clean the raw materials, avoiding the influence of insufficient raw material purity or surface oxidation on the later processing of the alloy. If irregular zirconium - cobalt raw materials are selected, the miscellaneous items in the melted zirconium - cobalt alloy material are obvious.

[0026] Preferably, in step (2), the equipment model of the magnetic levitation melting furnace is ZKYN - XFRL - 30; the vacuum environment is an environment with a vacuum degree lower than 3×10 -3 Pa. Under these conditions, the product purity can be guaranteed.

[0027] Preferably, in step (2), a 30 kg electromagnetic levitation melting furnace (equipment model: ZKYN-XFRL-30) is used to wash the furnace with argon twice, and then the zirconium-cobalt mixed granular material is melted under an environment with a vacuum degree lower than 3×10 -3 Pa.

[0028] In the present invention, an electromagnetic levitation melting equipment (equipment model: ZKYN-XFRL-30) is used to melt the zirconium-cobalt elemental materials. Compared with the traditional intermediate frequency melting, the electromagnetic levitation melting avoids the pollution of the materials by the crucible, provides better guarantee for the processing of the zirconium-cobalt alloy, and through this step, a high-purity phase zirconium-cobalt alloy rod is obtained.

[0029] Preferably, in step (2), the heating rate of the slow heating is 10-20 °C / min; the holding time is 1-3 h.

[0030] Preferably, in step (2), the melting parameters are as follows: heating to 2050-2100 °C at a heating rate of 14-16 °C / min for holding, and the holding time is 1.5-2 h; after the holding is completed, cooling to 300-350 °C at a cooling rate of 10-15 °C / min. Under this condition, the cracking of the alloy can be avoided to the greatest extent, and a complete and uniform ingot can be obtained.

[0031] Preferably, after cooling to room temperature in step (2), turn it over, and repeat step (2) 3-4 times to obtain a ZrCo alloy single-phase ingot. Repeating step (2) multiple times, that is, adopting repeated melting, mainly solves the problem of serious segregation of the obtained zirconium-cobalt alloy powder caused by uneven fusion of zirconium and cobalt during the melting process, avoids the occurrence of anisotropic differences in physical properties, and avoids the decline of mechanical properties.

[0032] Preferably, in step (3), the equipment model of the rotating electrode powder making equipment is ZKYN-PLRP-18000.

[0033] Preferably, in step (3), the working conditions of the rotating electrode powder making are as follows: rotating powder making is carried out under the working conditions of a vacuum degree of 0.01±0.001 Pa, an electrode rotation speed of 14500-15500 R / min, and a power of 80-85 KW.

[0034] A power of 80 - 85 KW can reach the melting point of zirconium cobalt alloy, melting its surface. If the power is too small, it cannot melt; if the power is too large, the melting is too fast and the sphericity of the powder made is not high. When the rotation speed is higher than 15500 R / min, the yield of the target size decreases. When the rotation speed is lower than 14500 R / min, the centrifugal force is too small and the sphericity of the obtained powder decreases. Under these working conditions, a cobalt zirconium alloy material with a target particle size of 50 - 150 um is obtained, with a high yield, and the yield reaches more than 70%. Through multiple verifications, the present invention has obtained zirconium cobalt alloy powder with ultra-high sphericity. Due to the high activity of zirconium alloy, the requirements for the sphericity of preparing spherical powder are relatively high, and the particle size range is strictly required. When the particle size is less than 50 um, the activity of cobalt zirconium alloy powder gradually increases, and it will spontaneously combust with a slight collision at 100°C.

[0035] Preferably, in step (3), the diameter of the cylindrical cobalt zirconium alloy rod is 50 mm and the length is 370 mm.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1. Since conventional hydrogen storage alloy materials have high activity, risks such as spontaneous combustion are likely to occur during their manufacturing, transportation, and processes. By changing the microscopic morphology of the hydrogen storage material, the present invention improves the sphericity of spherical powder. The prepared spherical zirconium cobalt hydrogen storage powder has ultra-high sphericity, good fluidity, less pollution, high yield, no edges and corners on the surface, a smooth surface, a relatively high hydrogen storage capacity. The hydrogen storage capacity at 0.15 MPa can reach more than 2.8 wt%. More importantly, it reduces the specific surface area of the powder, reduces the activity of the hydrogen storage material, avoids the dangers during manufacturing, transportation, and storage, is not easy to powderize and oxidize, has good hydrogen storage performance cyclicity, solves the problems of existing hydrogen storage alloy powder being prone to spontaneous combustion risks during manufacturing, transportation, and processes, and poor safety in transportation and storage. It has high safety, good cyclicity of hydrogen absorption and hydrogen release performance, is a hydrogen storage material with high stability, easy to store and transport, and is suitable for large-scale applications. It is applicable to scenarios with high stability and long lifespan requirements, such as hydrogen storage alloy materials in vehicle-mounted hydrogen storage systems, fixed hydrogen storage systems, nuclear industry, aerospace and other fields.

[0038] 2. The zirconium cobalt alloy hydrogen storage material prepared by the present invention has mild hydrogen absorption and hydrogen release reaction conditions, can still maintain high performance after multiple hydrogen absorption and hydrogen release cycles, and performs well in high-temperature and corrosive environments.

[0039] 3. During the casting and cooling process of the present invention, it is not prone to cracking and can obtain a complete ingot, solving the problem that the alloy rod material required for preparing spherical powder is brittle and prone to cracking. Through a large number of experiments, the present invention selects a zirconium-cobalt molar ratio of 1:0.99 - 1.01, which has high hydrogen storage performance, is easy to form, will not crack during the casting and cooling process, and can obtain a complete ingot. When the zirconium content is too high, the zirconium-cobalt alloy becomes brittle and will crack during the casting and cooling process of preparing the alloy, and a complete ingot required for powder preparation cannot be obtained. When the zirconium content is too low, the hydrogen storage performance is low.

[0040] 4. Due to the high activity of zirconium alloy, the sphericity requirement for preparing spherical powder is relatively high, and the particle size range requirement is strict. Through multiple verifications, the present invention obtains the target zirconium-cobalt alloy powder with ultra-high sphericity. Brief Description of the Drawings

[0041] Figure 1 is the SEM image of the spherical zirconium-cobalt hydrogen storage powder prepared in Example 1;

[0042] Figure 2 is another SEM image of the spherical zirconium-cobalt hydrogen storage powder prepared in Example 1;

[0043] Figure 3 is the quality inspection form of the single-element zirconium particles used in the example;

[0044] Figure 4 is the quality inspection form of the single-element cobalt particles used in the example;

[0045] Figure 5 is the XRD pattern of the ZrCo alloy single-phase ingot obtained in step (3) of Example 1;

[0046] Figure 6 is the hydrogen absorption capacity test chart of the spherical zirconium-cobalt hydrogen storage powder prepared in Example 1;

[0047] Figure 7 is the SEM image of the zirconium-cobalt alloy powder prepared in Comparative Example 9;

[0048] Figure 8 is the SEM image of the zirconium-cobalt alloy powder after being used once in Comparative Example 9. Detailed Embodiments

[0049] The following further illustrates the present invention through specific examples. The examples described in the present invention are only for the illustration of the present invention and do not limit the scope of the present invention.

[0050] Analyze the single-element zirconium particles and single-element cobalt particles used in the examples of the present invention. Select cylindrical particles with φ3*3mm as samples and use a ZKYN-ICP-01 analyzer for analysis. The quality inspection form of the single-element zirconium particles used in the examples of the present invention is shown in Figure 3, the quality inspection form of the single cobalt particles used is shown in Figure 4 .

[0051] The magnetic levitation melting furnace can use conventional commercially available equipment. In this embodiment, the equipment model is: ZKYN-XFRL-30.

[0052] The rotating electrode powder making equipment can use conventional commercially available equipment. In this embodiment, the equipment model is: ZKYN-PLRP-18000.

[0053] Example 1

[0054] The present invention provides a preparation method of a zirconium-cobalt hydrogen storage material, comprising the following steps:

[0055] (1) Select single zirconium particles with a purity of 99.96%, the single zirconium particles are cylindrical particles with a diameter of 3 mm and a length of 3 mm, single cobalt particles with a purity of 99.95%, the single cobalt particles are cylindrical particles with a diameter of 3 mm and a length of 3 mm. Mix the single zirconium particles and the single cobalt particles in a 1:1 equimolar ratio to obtain a zirconium-cobalt mixed particle material with a charge of 30000 g;

[0056] (2) Use a 30 kg magnetic levitation melting furnace (equipment model: ZKYN-XFRL-30) to perform argon furnace washing 2 times and then melt the zirconium-cobalt mixed particle material under an environment with a vacuum degree lower than 3×10 -3 Pa. The melting parameters are as follows: heat up to 2100 °C at a heating rate of 15 °C / min for heat preservation, and the heat preservation duration is 2 h; after the heat preservation is completed, cool down to 340 °C at a cooling rate of 15 °C / min, and then cool with the furnace to room temperature;

[0057] (3) Then turn over the alloy material obtained after cooling in step (2), put it into a crucible and repeat step (2) 3 times in the magnetic levitation melting furnace, and perform a total of 4 meltings on the zirconium-cobalt alloy to obtain a ZrCo alloy single-phase alloy ingot without other impurity phases;

[0058] (4) Through lathe processing, remove the surface oxide layer and the possibly contaminated surface layer of the ZrCo alloy single-phase alloy ingot obtained in step (3) to obtain a cobalt-zirconium alloy rod with a diameter of 50 mm and a length of 370 mm. Perform plasma rotating electrode (PREP) powder making on the cobalt-zirconium alloy rod in a rotating electrode powder making equipment (equipment model: ZKYN-PLRP-18000). The working conditions of powder making are: vacuum degree 0.01 Pa, electrode rotation speed 15000 R / min, power 80 KW. After powder making, spherical zirconium-cobalt hydrogen storage powder with a target size of 50 - 150 μm and a mass ratio of more than 70% is obtained.

[0059] The SEM diagram of the spherical zirconium-cobalt hydrogen storage powder is shown in Figure 1 andFigure 2 , from Figure 1 It can be seen that the spherical zirconium-cobalt hydrogen storage powder prepared by the present invention has a high sphericity, no sharp edges on the surface, and a smooth surface. Figure 2 It can be seen that D90 is in the range of 50 - 150 μm, which is an ideal particle size.

[0060] Select a 10*10*1 mm alloy sheet of the ZrCo alloy single-phase alloy ingot obtained in step (3) as a sample, and use a ZKYN-XRD-1 X-ray diffractometer for detection. The XRD pattern is shown in Figure 5 , and it can be seen that the main phase of the sample is ZrCo, and no impurity phase is detected.

[0061] Select the spherical zirconium-cobalt hydrogen storage powder prepared in Example 1 as a sample. According to the test method of the P-C-T curve: at a temperature of 25 °C, use a Sienelts device to perform hydrogen absorption and desorption tests on the sample. The test diagram is shown in Figure 6 , from which it can be seen that the hydrogen absorption capacity of the sample reaches 2.9 wt%.

[0062] Example 2

[0063] The present invention provides a preparation method of a zirconium-cobalt hydrogen storage material, including the following steps:

[0064] (1) Select single-element zirconium particles with a purity of 99.96%, the single-element zirconium particle specification is a cylindrical particle with a diameter of 3 mm and a length of 3 mm, single-element cobalt particles with a purity of 99.95%, and the single-element cobalt particle specification is a cylindrical particle with a diameter of 3 mm and a length of 3 mm. Mix the single-element zirconium particles and the single-element cobalt particles according to an equimolar ratio of 1:1 to obtain a zirconium-cobalt mixed particle material with a charge of 30000 g;

[0065] (2) Use a 30 kg magnetic levitation melting furnace (equipment model: ZKYN-XFRL-30) to perform argon furnace washing 2 times, and then melt the zirconium-cobalt mixed particle material in an environment with a vacuum degree lower than 3×10 -3 Pa. The melting parameters are as follows: heat up to 1950 °C at a heating rate of 10 °C / min for heat preservation, and the heat preservation duration is 3 h; after heat preservation, cool down to 300 °C at a cooling rate of 10 °C / min, and then cool down to room temperature with the furnace;

[0066] (3) Then turn over the alloy material obtained after cooling in step (2), put it into a crucible, and repeat step (2) 4 times in the magnetic levitation melting furnace. A total of 5 meltings are performed on the zirconium-cobalt alloy to obtain a ZrCo alloy single-phase alloy ingot without other impurity phases;

[0067] (4) By turning processing, remove the surface oxide layer and the possibly contaminated surface layer of the ZrCo alloy single-phase ingot obtained in step (3) to obtain a cobalt-zirconium alloy rod with a diameter of 50 mm and a length of 370 mm. Perform plasma rotating electrode process (PREP) powder making on the cobalt-zirconium alloy rod in a rotating electrode powder making equipment (equipment model: ZKYN-PLRP-18000). The operating conditions for powder making are: vacuum degree 0.01 Pa, electrode rotation speed 15000 R / min, power 80 KW. After powder making, the mass ratio of the target size in the range of 50 - 150 μm is more than 75%, and spherical zirconium-cobalt hydrogen storage powder is obtained.

[0068] SEM test shows that the prepared spherical zirconium-cobalt hydrogen storage powder has a high sphericity, no edges and corners on the surface, a smooth surface, D90 is in the range of 50 - 150 μm, and the hydrogen absorption capacity reaches 2.9 wt%.

[0069] Comparative Example 1

[0070] A spherical zirconium-cobalt hydrogen storage material and its preparation method are basically the same as those in Example 1, the only difference being that: the molar ratio of zirconium to cobalt is 60%:40%.

[0071] Result: The zirconium-cobalt alloy obtained in steps (2) and (3) is relatively brittle and cracks during the cooling process, and a complete ingot meeting the powder making requirements cannot be obtained.

[0072] Comparative Example 2

[0073] A spherical zirconium-cobalt hydrogen storage material and its preparation method are basically the same as those in Example 1, the only difference being that: the molar ratio of zirconium to cobalt is 40%:60%.

[0074] Result: The hydrogen storage performance of the obtained spherical zirconium-cobalt hydrogen storage powder is low. Under the same working condition environment as in Example 1, the hydrogen absorption capacity is only 1.8%.

[0075] Comparative Example 3

[0076] A spherical zirconium-cobalt hydrogen storage material and its preparation method are basically the same as those in Example 1, the only difference being that: in step (1), the elemental zirconium particles and elemental cobalt particles are mixed in an equimolar ratio of 1:1, and then 8% of Mn based on the total molar ratio of zirconium-cobalt particles is added to prepare a ternary alloy hydrogen storage material.

[0077] Result: During the melting in steps (2) and (3), the alloy components are relatively brittle and crack during the cooling process, and a complete ingot meeting the powder making requirements cannot be obtained.

[0078] Comparative Example 4

[0079] A spherical zirconium-cobalt hydrogen storage material and its preparation method are basically the same as those in Example 1, except that in step (1), elemental zirconium particles and elemental cobalt particles are mixed in a molar ratio of 1:1, and then 10% of Fe based on the total molar ratio of zirconium-cobalt particles is added to prepare a ternary alloy hydrogen storage material.

[0080] Result: During the melting in steps (2) and (3), the alloy components were all brittle and cracked during the cooling process, and a complete ingot meeting the powder making requirements could not be obtained.

[0081] Comparative Example 5

[0082] A spherical zirconium-cobalt hydrogen storage material and its preparation method are basically the same as those in Example 1, except that in step (2), an intermediate frequency melting furnace is used for melting.

[0083] Result: The segregation of the melted zirconium-cobalt alloy was obvious, with impurity peaks of elemental zirconium and cobalt. The proportion of the zirconium-cobalt alloy measured by XRD was only 94%, with obvious miscellaneous items.

[0084] Comparative Example 6

[0085] A spherical zirconium-cobalt hydrogen storage material and its preparation method are basically the same as those in Example 1, except that in step (4), atomization powder making (EIGA) is used for powder making.

[0086] The process of atomization powder making (EIGA) is as follows: High-pressure (8 - 10 Mpa) argon gas is ejected at a supersonic speed of 2.1 Mach through a coupling nozzle, and the surface of the molten zirconium-cobalt alloy rod is broken into tiny droplets by the gas flow. The zirconium-cobalt alloy droplets are cooled and solidified into spherical powders in a very short time. The powders fall into the collection tank after cooling through the settling chamber. The collected powders are sieved under argon protection to obtain the target powders with a size of 50 - 150 um, and the yield is 40.2%, which is relatively low and not ideal.

[0087] Comparative Example 7

[0088] A spherical zirconium-cobalt hydrogen storage material and its preparation method are basically the same as those in Example 1, except that step (3) is omitted, that is, the zirconium-cobalt alloy is melted only once in total.

[0089] Result: The segregation of the melted zirconium-cobalt alloy was obvious, with impurity peaks of elemental zirconium and cobalt. The zirconium-cobalt alloy phase accounted for only 85% measured by XRD.

[0090] Comparative Example 8

[0091] A spherical zirconium-cobalt hydrogen storage material and its preparation method are basically the same as those in Example 1, except that in step (2), the cooling rate is 30 °C / min.

[0092] Result: Cracking of the alloy occurred during the cooling process in step (2), and a complete ingot meeting the powder making requirements could not be obtained.

[0093] Comparative Example 9

[0094] A spherical zirconium-cobalt hydrogen storage material and its preparation method are basically the same as those in Example 1, and the only difference is that: steps (1)-(3) are the same as those in Example 1, and step (4) is: through lathe processing, the surface oxide layer and the possibly contaminated surface layer of the ZrCo alloy single-phase ingot obtained in step (3) are removed to obtain a cobalt-zirconium alloy rod with a diameter of 50 mm and a length of 370 mm, and the cobalt-zirconium alloy rod is mechanically crushed to obtain zirconium-cobalt alloy powder.

[0095] The obtained zirconium-cobalt alloy powder was subjected to SEM testing, and the SEM images are shown in Figure 7 , from Figure 7 It can be seen that the zirconium-cobalt alloy powder is irregular, has many surface edges and corners, and is not smooth, which will exacerbate pulverization, cause oxidation and safety problems, and the cyclicity of hydrogen storage performance is poor.

[0096] The zirconium-cobalt alloy powder obtained in Comparative Example 9 was used once (hydrogen absorption for 10 hours and hydrogen desorption for 5 hours at a temperature of 25-30 °C), and then subjected to SEM testing. The SEM images after use are shown in Figure 8 , from Figure 8 It can be seen that after being used once, the pulverization is serious, and after hydrogen desorption, it is prone to spontaneous combustion and has a low safety factor.

Claims

1. A preparation method of a zirconium-cobalt hydrogen storage material, characterized in that: It includes the following steps: (1) Select elemental zirconium particles and elemental cobalt particles, and mix them in a molar ratio of 1:0.99 - 1.01 to obtain a zirconium-cobalt mixed particle material; (2) Use a magnetic levitation melting furnace to melt the zirconium-cobalt mixed particle material in a vacuum environment. The melting parameters are as follows: slowly heat up to 1950 - 2200 °C for heat preservation; after heat preservation, cool down to 300 - 350 °C at a cooling rate of 10 - 20 °C / min, and then cool with the furnace to room temperature to obtain a ZrCo alloy single-phase ingot without other impurity phases; (3) Through lathe processing, remove the surface layer of the ZrCo alloy single-phase ingot obtained in step (2) to obtain a cylindrical cobalt-zirconium alloy rod. Perform plasma rotating electrode atomization powder making on the cobalt-zirconium alloy rod in a rotating electrode powder making device. After powder making, spherical zirconium-cobalt hydrogen storage powder with a target size of 50 - 150 μm is obtained.

2. The preparation method of the zirconium-cobalt hydrogen storage material according to claim 1, wherein: In step (1), the elemental zirconium particles are cylindrical particles with a diameter of 3 mm and a length of 3 mm; the elemental zirconium particles are cylindrical particles with a diameter of 3 mm and a length of 3 mm.

3. The preparation method of the zirconium-cobalt hydrogen storage material according to claim 1, characterized in that: In step (2), the equipment model of the electromagnetic levitation melting furnace is ZKYN-XFRL-30; the vacuum environment is an environment with a vacuum degree lower than 3×10 -3 Pa.

4. The preparation method of the zirconium-cobalt hydrogen storage material according to claim 1, characterized in that: In step (2), the heating rate for slow heating is 10 - 20 °C / min; the heat preservation time is 1 - 3 h.

5. The preparation method of the zirconium-cobalt hydrogen storage material according to claim 4, characterized in that: In step (2), the melting parameters are as follows: heat up to 2050 - 2100 °C at a heating rate of 14 - 16 °C / min for heat preservation, and the heat preservation duration is 1.5 - 2 h; after heat preservation, cool down to 300 - 350 °C at a cooling rate of 10 - 15 °C / min.

6. The preparation method of the zirconium-cobalt hydrogen storage material according to claim 1, characterized in that: After cooling the product in step (2) to room temperature, turn it over and repeat step (2) 3 - 4 times to obtain a ZrCo alloy single-phase ingot.

7. The preparation method of the zirconium-cobalt hydrogen storage material according to claim 1, characterized in that: In step (3), the device model of the rotating electrode powder making device is ZKYN-PLRP-18000.

8. The preparation method of the zirconium-cobalt hydrogen storage material according to claim 1, characterized in that: In step (3), the working conditions for rotating electrode powder making are: perform rotating powder making under the working conditions of a vacuum degree of 0.01 ± 0.001 Pa, an electrode rotation speed of 14500 - 15500 R / min, and a power of 80 - 85 KW.

9. The preparation method of the zirconium-cobalt hydrogen storage material according to claim 1, characterized in that: In step (3), the diameter of the cylindrical cobalt-zirconium alloy rod is 50 mm and the length is 370 mm.

10. A zirconium-cobalt hydrogen storage material prepared by the preparation method according to any one of claims 1 - 9.

Citation Information

Patent Citations

  • Method for rapidly and efficiently activating ZrCo-based hydrogen isotope storage material

    CN105385975A

  • Hydrogen storage material doped with V and capable of improving performance of ZrCo hydrogen storage alloy and preparation method of hydrogen storage material

    CN112779439A

  • High-toughness corrosion-resistant zirconium-cobalt binary alloy and preparation method thereof

    CN114318057A

  • Nano-scale ZrCo alloy prepared by chemical method and preparation method of nano-scale ZrCo alloy

    CN114769607A

  • Hydrogen-gas discharge lamp

    US5543687A